Structural Analysis of Reinforced Concrete Column Dimensions in a Two-Story Building Using the Response Spectrum Method (Case Study: Villa Mahesa Anyer) - Nofiana, Tiara; Cahyadi, Cahyadi; Kurniazaki, Muhammad Khafidin (Jurnal Fondasi, 2026)
The construction of a two-story building in an earthquake-prone area required a structural design that was safe, efficient, and compliant with standards. One of the key elements in such a design was the dimension of flat reinforced concrete columns, which were often selected for their space efficiency and aesthetic value. This study compared the column dimensions of three configurations: Alternative 1 with all flat columns, Alternative 2 with all square columns, and the existing structure combining flat and square columns, to determine whether each configuration met the earthquake resistance criteria based on SNI 1726:2019. This research employed a quantitative method using numerical modeling with SAP2000 student version software. The seismic analysis was conducted using the response spectrum method in accordance with SNI 1726:2019, with a case study of Villa Mahesa, a two-story building located in Serang Regency. The analyzed loads included dead loads, live loads, wind loads, and earthquake loads. The analysis results showed that Alternative 1 had a maximum displacement of 4.32 mm, a deflection of 0.85 mm, a stress ratio of 0.50, and internal forces of Pu = 121.99 kN and Mu = 18.13 kNm, with an interaction value of 0.96 < 1.00, indicating safety. The existing columns exhibited a displacement of 3.12 mm, a deflection of 0.78 mm, and a stress ratio of 0.32, but had an interaction value of 1.24 > 1.00, indicating that they were unsafe. Meanwhile, Alternative 2 produced the smallest deformation (displacement of 2.45 mm and deflection of 0.66 mm) but had an interaction value of 1.11 > 1.00, which did not meet the structural strength criteria. Based on these findings, Alternative 1 was recommended as the most optimal column design for two-story buildings in earthquake-prone areas.